Implementasi Kemandirian dan Jiwa Sosial (Life Skills) Santri di Pesantren - Riyan (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
Education institutions in Indonesia generally expect the graduates to obtain jobs that are in line with the areas in which they are engaged when studying. But the hope is only a small part of the education in islamic boarding school which is expecting the graduates to be students who have the ability or self-skills, have a high social spirit and solidarity, good manners, Devoted to both parents and dedicated to the nation, state and religion. Therefore, the importance of the role and function of islamic boarding school to provide personal and social life skills. Personal and social life will be taught in Pondok Pesantren including the independence of students and the development of social souls (mutual help and foster the spirit of fellow students cooperation). This research is a qualitative study, with observation methods, interviews and documentation. The results show that first, the strategy of islamic boarding school Pangeran Diponegoro in the development of students independence is Kiai and the caregivers give advice, train the spirit of students leadership, familiarize the students in doing Activities in accordance with the regulations, the example of Kiai. Secondly, the strategy in social soul development by familiarizing students cares, maintaining togetherness, interacting, and behaving of sympathy and empathy.